2013
DOI: 10.1007/s10616-013-9572-4
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a mammalian cell line suitable for industrial production of recombinant protein using mutations induced by high-energy beam radiation

Abstract: Mammalian cells are extensively used for production of biopharmaceuticals. Most cells used in industry have infinite proliferative capacity, which provides a high number of cells and corresponding productivity. However, infinite cells will continue to multiply even after cell density reaches sufficient levels. This excess proliferation aggravates the culture environment and induces low productivity. Therefore, after cell density reaches sufficient levels, downregulation of proliferation would prevent such aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…4A,B and Tables 1-3). The number of CHO cells increased from 4450 seeding cells/well to 8190 cells/well after 24 h of culture, which is consistent with the 24 h doubling time reported by Chida et al, 17 indicating that the CHO cells were healthy and not damaged by PRF mixing. Supplemental Figure S17 is a photomicrograph of normalappearing CHO monolayers from microplate 1 after 24 h of incubation.…”
Section: Gentle Suspensionsupporting
confidence: 89%
See 1 more Smart Citation
“…4A,B and Tables 1-3). The number of CHO cells increased from 4450 seeding cells/well to 8190 cells/well after 24 h of culture, which is consistent with the 24 h doubling time reported by Chida et al, 17 indicating that the CHO cells were healthy and not damaged by PRF mixing. Supplemental Figure S17 is a photomicrograph of normalappearing CHO monolayers from microplate 1 after 24 h of incubation.…”
Section: Gentle Suspensionsupporting
confidence: 89%
“…The cells had nearly doubled to 8190 cells/well from the seeding number of 4450 CHO cells. Chida et al 17 have reported that the doubling time for CHO cells is reported to be ~24 h. The standard deviation between all 384 wells was 278 cells, with a coefficient of variation of 3.9%. A photomicrograph of the well monolayers illustrated a normal morphology (Suppl.…”
Section: Viability Of Cells After Prf Mixingmentioning
confidence: 99%